The Effectiveness of Taro Compost Fertilizer on Soil pH, Growth and Yield of Pak Choy (Brassica rapa L.) in Tasikmalaya - Adinda Putri Amanda; R. Arif Malik Ramadhan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Lack of awereness about the use of agriculture waste in increasing soil fertility leading to high use of inorganic fertilizer. Continuous use of inorganic fertilizer can reduce soil fertility in the future. This research aims to determine the impact of providing taro compost fertilizer on soil pH, growth and yield of pak choy In Tasikmalaya. This research was carried out in experimental field of Agriculture Faculty, Universitas Perjuangan Tasikmalaya from October until November 2023. Experimental design used a randomized block design of one factor with six treatments and three replications. The treatments consist of without taro compost fertilizer, 100, 150, 200, 250 and 300 g/polybag taro compost fertilizer. Reseach results show taro compost fertilizer can increase plant height, fresh weight of the plant, plant root length, fresh weight of roots and plant canopy weight. The best treatment was 300 g/polybag with plant height 16,8 cm, fresh weight of plant 55,63 g, plant root length 15,83 cm, fresh weight of roots 8,63 g, and plant canopy weight 47 g compared to control treatment without taro compost fertilizer. However, addition various doses taro compost fertilizer hasn’t effect for soil pH. The conclution of this research is that giving various doses of compost fertilizer can increase the growth and yield of pak choy in Tasikmalaya.